CHARACTERIZATION OF BIOACTIVE COMPOUNDS OF PORTUGUESE OYSTER Crassostrea angulata FROM BATU KARAS ESTUARY - Puji Hastuti Kusumawati; Neviaty P Zamani; Dedi Soedharma; Nurjanah Nurjanah (Jurusan Perikanan dan Kelautan, 2023)
Portuguese oyster C. angulata is one of the potential source of bioactive compounds from estuary in Indonesia, especially from Batu Karas Village Pangandaran District. The aims of this research were to explore and characterize the bioactive compounds of the estuary oyster. The oyster separated from the shell, and then extracted in ethanol solvent with orbital maseration method in 24 hours. After filtration and evaporation, bioactive extract were characterized with qualitative phytochemical method. The extraction resulted 3.42% yield. Bioactive compound of the oyster has phytochemical characters, respectively, alkaloid, flavonoid, and fenol hidroquinon positives. The oyster bioactive compounds need to characterize with quantitative method, and biological activityies analysis futher more.Keywords: cupped oysters, secondary metabolites